Adopting Theories Underlying Directed Technology Integration Strategies: Study Objectivist Learning Theories - Fajri Asshdiqi, Ahmad (Jurnal Ilmiah Mandala Education (JIME), 2024)
This paper examines key theories underlying directed technology integration strategies in education, focusing on objectivist learning approaches. The study reviews and analyzes several influential theories, including B.F. Skinner's behaviorism, Atkinson and Shiffrin's information processing model, Robert Gagne's conditions of learning, and systems theory approaches to instructional design.The analysis reveals how these theories provide conceptual foundations for technology integration in education. Behaviorism emphasizes reinforcement and observable outcomes. Information processing theory explains memory and cognitive processes. Gagne's work highlights conditions for effective learning. Systems approaches offer frameworks for designing technology-enhanced instruction. While each theory offers valuable insights, an integrated approach incorporating behaviorist, cognitive, and constructivist perspectives may be most effective for technology-enhanced learning. Understanding these theoretical underpinnings can guide educators in developing more effective technology integration strategies and creating optimal learning conditions in digital environments. This paper synthesizes key objectivist learning theories relevant to educational technology, providing a theoretical foundation to inform technology integration practices in modern education.